2012
DOI: 10.1002/ana.23693
|View full text |Cite
|
Sign up to set email alerts
|

Cortical remyelination: A new target for repair therapies in multiple sclerosis

Abstract: Objective Generation and differentiation of new oligodendrocytes in demyelinated white matter is the best described repair process in the adult human brain. However, remyelinating capacity falters with age in patients with multiple sclerosis. (MS). Since demyelination of cerebral cortex is extensive in brains from MS patients, we investigated the capacity of cortical lesions to remyelinate and directly compared the extent of remyelination in lesions that involve cerebral cortex and adjacent subcortical white m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
209
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(226 citation statements)
references
References 42 publications
10
209
2
2
Order By: Relevance
“…The generation of new OPCs and myelin can be observed in white matter lesions at the early stages of the disease (Prineas et al 1993;Lucchinetti et al 1999;Chang et al 2012), while the majority of chronically demyelinated lesions in white matter demonstrate restricted remyelination due to a reduced recruitment of OPCs, the failure of OPCs to produce mature oligodendrocytes, and the insufficient production of myelin sheath by OLs (Trapp et al 1997;Wolswijk 2000;Chang et al 2002;Kuhlmann et al 2008;Chang et al 2012). Importantly, it was also shown that in the corpus callosum, premyelinating OLs usually occur in groups and their processes overlap extensively, which allows the clusters of OLs to compete more effectively for the survival factors in the neighborhood (Trapp et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The generation of new OPCs and myelin can be observed in white matter lesions at the early stages of the disease (Prineas et al 1993;Lucchinetti et al 1999;Chang et al 2012), while the majority of chronically demyelinated lesions in white matter demonstrate restricted remyelination due to a reduced recruitment of OPCs, the failure of OPCs to produce mature oligodendrocytes, and the insufficient production of myelin sheath by OLs (Trapp et al 1997;Wolswijk 2000;Chang et al 2002;Kuhlmann et al 2008;Chang et al 2012). Importantly, it was also shown that in the corpus callosum, premyelinating OLs usually occur in groups and their processes overlap extensively, which allows the clusters of OLs to compete more effectively for the survival factors in the neighborhood (Trapp et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of myelination, OPCs, and OLs were processed as previously described (Dutta et al 2011;Chang et al 2012;Sachs et al 2014). Briefly, free-floating sections (30 μm) of the corpus callosum were stained with antibodies to PLP (Cleveland Clinic Hybridoma), PDGFRα (Cell Signaling), and GSTpi (Assay Designs) to quantify myelin, OPCs, and OLs, respectively.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In MS, repair and remyelination occur in shadow plaques (Chang et al, 2012) but, as the disease progresses, remyelination becomes less efficient (Chang et al, 2002;Franklin, 2002;Goldschmidt et al, 2009). It is unlikely that the inability to remyelinate results from the absence of oligodendrocyte precursor cells (OPCs) in the adult CNS, as OPCs are present in elderly patients even decades after having been diagnosed with the disease (Chang et al, 2012). Alternatively, the failure in remyelination might reflect changes in the local extracellular environment, specifically those affecting the extracellular matrix (ECM) proteins and chondroitin sulfate proteoglycans (CSPGs).…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation could be that remyelination and repair across several cortical regions and the periventricular portion of the corticospinal tract, which could reflect concomitant pathophysiologic mechanisms normal-appearing WM of MS patients relative to control participants (37). Interestingly, we found an association between intracortical pathologic changes capacities, known to occur both in the cortex and in the WM (38,39), may be exceeded in cortical and WM regions not necessarily spatially connected. Some limitations apply to this study.…”
Section: Neuroradiology: Cortical and White Matter Pathologic Changesmentioning
confidence: 64%